NONLINEAR CHARACTERISTICS OF HERRINGBONE GEAR FOUR-BRANCHING TRANSMISSION CONSIDERING GEAR BACKLASH EFFECT - DONG Hao; FANG ZongDe; FANG Zhou; ZHAO XiaoLong (Jixie qiangdu)
For the nonlinear problem of herringbone gear power transmission four heavy branch by analysis of backlash of the ship,combined with the theory of the concentrated parameter,considering the time-varying stiffness,mesh damping,brace stiffness and damping,dynamic model of backlash nonlinear factors. With herringbone gear loaded tooth contact method of simulation technology,put forward a method for accurate calculation of herringbone gear meshing stiffness excitation; By using the theory of the concentrated parameter,three-dimensional dynamic model of bending torsion coupling of the system is established;Based on the dynamic differential equations are solved with variable step four order Runge-Kutta method,obtained under the influence of backlash in the system without impact,dynamic load coefficient and amplitude of unilateral and bilateral shock state.The results show that Power four branch transmission system has a complex nonlinear characteristic,which is sensitive to the change of the tooth side gap,the influence of the backlash on the nonlinear characteristics is greater,and the system load changes from the side impact to the side impact of the system when the backlash is changed from 0 μm 150 μm; When the tooth gap is greater than a certain critical value,the dynamic characteristics of the system will not change with the increase of the gap of the tooth. To reveal the variation of nonlinear dynamic characteristics of herringbone gear power transmission for the four branching,the system dynamic equilibrium optimization design has laid a theoretical foundation.